Debt heterogeneity, agency costs and business risk of multinational corporations - Khaw, Lee-Hwei; Batten, Jonathan A.; Young, Martin R. (2014)
Internationalization enables multinational corporations (MNCs) to diversify their source and type of debt as well as earnings, although doing so incurs agency costs of debt and business risk.To mitigate these costs, existing studies find that MNCs typically have lower levels of long-term debt than domestic corporations (DCs). One key limitation of these studies is their failure to recognize the heterogeneity of debt, specifically the equity options embedded in the debt issued by MNCs. We show that in the presence of agency costs of debt and business risk, MNCs are able to mitigate the negative effects on long-term debt by utilizing convertible debt in their debt structure, as compared to DCs. Therefore, MNCs are able to sustain higher levels of long-term debt to make the most from international diversification. Relatively, the significance of business risk is found to out weigh the significance of agency costs as MNCs further increase their degree of internationalization.Evidence also shows that the issuers of convertible debt are not dominated by smaller and riskier growth firms, but is linked to internationalization.